Criminological Study On Children As Actors Of The Crime Of Theft - Yunita Lestari (Jurnal Hukum Khaira Ummah, 2022)
This paper aims to find out and the factors that cause children to commit the crime of theft are studied criminologically, in this study using an empirical juridical writing method, namely research conducted on the real situation of society or the community environment with the intent and purpose of finding facts, which then leads to identification and ultimately leading to problem solving with data sources obtained directly through field observations and interviews with respondents regarding children who are perpetrators of the crime of theft.The results of this study are that the factors that cause children to commit the crime of theft are caused by several kinds of factors, namely economic factors, family factors, educational factors, and environmental factors. good morals and morals so that children do not commit crimes, besides that community participation is no less important in building a safe, orderly, and child-friendly environment.